Electrical and photoelectrical properties of zn1−xMgxO Thin Films Obtained by Spin Coating and Aerosol Deposition Method - Morari, V.; Postolache, V.; Mihai, Geanina Valentina; Rusu, E.; Monaico, Ed.; Ursachi, V. V.; Nielsch, Kornelius; Tiginyanu, I. M. (IFMBE Proceedings, 2020)
Zn1−xMgxO thin films were prepared by aerosol deposition and spin-coating method, using zinc acetate and magnesium acetate as precursors. The obtained films were investigated by scanning electron microscopy (SEM), electrical and photoelectrical characterization. SEM and energy dispersive x-ray (EDX) analysis has shown that the produced thin films are homogeneous in morphology and composition. The relaxation of photoconductivity under UV illumination was investigated in vacuum as a function of temperature. It was found that the thin films produced by spin-coating exhibit much higher photosensitivity and long duration relaxation of photoconductivity, in contrast to the films obtained by aerosol deposition. The investigation of photosensitivity in a wider spectral range demonstrated that the films are also sensitive to the visible and infrared irradiation.
CRIS-Team Scopus Importer:2022-04-14
Keywords: I-V characterization; SEM; Semiconductors; UV radiation; ZnMgO